Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an assessment of the monetary policy stance and broad financial conditions in Colombia, which provides insights about macro-financial linkages. It also discusses how nonfinancial corporate debt and leverage have increased in recent years, supported by easy access to capital markets, abundant global liquidity, and low interest rates. While some sectors look somewhat more strained than others (oil, gas, and airlines), debt servicing capacity has also improved with recent economic growth. This paper explores three possible drivers of inflation dynamics in Colombia: exchange rate pass-through, the El Nino meteorological phenomenon, and wages. The Colombian peso depreciated in line with the decline in oil prices, pushing up tradable-goods inflation.